Navigating customer experience: Insights into fast food satisfaction and happiness in Sarawak - Latip, Malisah; Nancy, Thien Swee Yen; Omar, Salmah (Universiti Teknologi MARA, 2023)
The rapid global expansion of the fast-food industry, predominantly driven by American multinational corporations, has significantly impacted consumer choices on a global scale. However, there is a lack of comprehensive research or insights into the unique factors that drive customer satisfaction and happiness in the Sarawak fast food sector. This gap exists because the dynamics of customer preferences, behaviours, and expectations can vary significantly from one region to another, and it is essential to understand these local nuances to improve the fast food industry's performance. To address this gap, this research sets out to achieve several objectives: (1) to identify the key factors that significantly influence customer satisfaction within Sarawak's fast food industry, focusing on perceived price, food quality, service quality, and the physical environment; and (2) to investigate the relationship between customer satisfaction and happiness. This study will use convenience sampling to collect primary data from fast-food consumers in Sarawak, utilizing a comprehensible five-point Likert scale questionnaire adapted from previous studies. The data will be analysed by Pearson's correlation and single linear regression with the Statistical Package for the Social Sciences (SPSS). The expected findings of this study include identifying significant factors influencing customer satisfaction and understanding the relationship between customer satisfaction and happiness, thus addressing the critical research gap specific to Sarawak's fast food industry. Ultimately, this research aims to contribute to the growth and success of Sarawak's fast food industry by fostering higher levels of customer satisfaction, happiness and the cultivation of long-term customer relationships.